Data registration in a first level child growth and development service - Segura, J. Luis (2006)
Objectives: To determine data registration time in a health center child growth and development service. Setting: Mi Peru Health Center, Callao Health Direction, Peru. Materials and Methods: Study by direct observation of the time used during consultation in 51 users of a growth and development service. Results: Five formats were used for data registration during consultation. Each time a child was attended 31 variables were registered; one variable was simultaneously registered in 5 formats, 3 variables in 6 formats, and 7 in 2 formats. The median time required for handwriting of all formats was 2,09 minutes, equivalent to 15,3% of the overall time used for the child attention. Conclusion: Data registration in the growth and development services demands a considerable proportion of the time available for consultation.